A study among women attending Suraksha clinic in a tertiary care hospital: their socio-demographic profile, myths and misconceptions related to RTIs - Singh, Aman Dev; Balgir, Rajinder Singh; Oberoi, Simmi; Jain, Ira; Jain, Ankur (International Journal Of Community Medicine And Public Health, 2017)
Background: Reproductive tract infections (RTIs) represent a vast reservoir of infections among women of reproductive age group observed more often in developing countries.Besides being a major public health problem RTIs and STDs are responsible for infections in post abortion & puerperal period, fetal and perinatal deaths, infertility and cervical cancer. These are a reason for emotional distress in women and a reason for their social rejection.Despite the ability to cure these infections, they continue to be a major public health problem worldwide especially in developing countries.Hence, a hospital based study was done amongst women of reproductive age group reporting to Rajindra Hospital Patiala with RTI, in terms of their socio-demographic profile, myths and misconceptions related to RTIs. Methods: This study was conducted with the objective of evaluating the socio-demographic profile, myths and misconceptions related to RTIs among reproductive age group women in Suraksha Clinic, Gynae OPD in Rajindra Hospital, Patiala from January 2014 to December 2014. A pretested structured Performa was used to collect data from 500 women with RTIs in 15-45 age group. Data was collected, compiled and analyzed statistically. Results: Out of 500 diagnosed patients of RTIs, only 120 (i.e. 24%) had various myths and misconceptions about reproductive tract infections and among them 40% had believe that vaginal discharge was normal phenomena. Majority of RTI patient 12% had bad physical hygiene. However 49.20% among them had poor menstrual hygiene. Conclusions: The influence of socio-demographic factors like age, educational status, socioeconomic status, menstrual hygiene also has its direct effect on occurrence of RTI in community.